Predictors of Appropriate Shocks and Ventricular Arrhythmia in Indonesian with Brugada Syndrome - Ardian Rizal; Sunu Budhi Raharjo; Dicky Armein Hanafy; Yoga Yuniadi (The Indonesian Heart Association, 2019)
Background : Brugada syndrome is an inherited disease characterized by an increased risk of sudden cardiac death owing to ventricular arrhythmias in the absence of structural heart disease. It has been reported that this syndrome is more prevalent in South-East Asia than in Western countries. Furthermore, genetic studies showed important contributions of several gene mutations to the phenotype of BrS. These suggest that ethnic difference play significant roles in the pathogenesis of BrS. In addition, ICD implantation remains the cornerstone management with a low rate of appropriate shocked. Therefore, it is important to investigate patients’ characteristics for risk stratification. Our objective to investigate the clinical, electrocardiography (ECG) and electrophysiological characteristics that can be used as predictor of appropriate shock due to ventricular arrhythmia (VA) in Indonesian patients with BrS. Methods : We analyse data from Brugada syndrome registry at National Cardiovascular Centre Harapan Kita since January 2013. Total 22 patients were included. Characteristics of BrS that we analysed were baseline characteristics (age and sex), Clinical finding (syncope, cardiac arrest), ECG finding (spontaneous type 1 or drug induced) and Electrophysiology study result (inducible VA and RV ERP). We also added some new ECG characteristic (S wave in lead 1, S wave duration in V1, Fragmented QRS, Junction ST elevation and early repolarization pattern in infero-lateral) to be analysed. Our end point are appropriate shock during ICD interrogation for those who have been implanted an ICD, and documented VA for those who didn’t receive ICD. Result : We found high incidence of appropriate ICD’s shock in our population (50% in our study vs 5-11.5% in real world). Predictors of appropriate shock and documented VA are history of syncope (p = 0.045; OR 2.57 [1.44-4.59]), spontaneous type-1 ECG (p = 0.005) and right ventricular effective refractory period (RV ERP) of <200 ms (p=0.018). Other parameters that have been reported to correlate with the occurrence of VA (S Wave in lead 1 (p = 0.530), early repolarization pattern (p = 0.578), fragmented QRS (p = 0.601), S Wave duration (p = 0.365) and J Point STE (p = 0.800) were found to be not correlated to appropriate shock in our populations. Conclusion : History of syncope, spontaneous type-1 Brugada ECG and RV ERP of <200 ms have predictive values for risk stratification of Indonesian patients with Brugada syndrome. Keywords : Brugada Syndrome, Ventricular arrhythmia, ICD shock